The Relationship Between Middle School Students' Attitudes Towards Mathematical Problem-Posing, Attitudes Towards Mathematical Problem-Solving, and Attitudes Towards Mathematics - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2019)
It was aimed to develop a scale for determining middle school students' attitudes towards mathematical problem-posing (First Study), and to present functionality of the developed scale and relationships between middle school students' mathematical problem-posing attitudes, mathematical problem-solving attitudes, and attitudes towards mathematics (Second Study). In the First Study, evidences regarding the reliability and validity of the scale were presented. It was proved that the scale is practicable. The Second Study which was designed according to relational scanning model. 444 middle school students participated in this study. Mathematical Problem-Posing Attitude Scale, Mathematical Problem-Solving Attitude Scale and Attitude Scale towards Mathematics were used as data collection instruments. It was determined that middle school students' mathematical problem-posing attitudes, mathematical solving attitudes, and attitudes towards mathematics were positive and high level. In addition, high-level relationships were identified between such attitudes of students. Lastly, it was determined that the female students had higher attitudes than the male students and these attitudes get lower as grade level rises.
Keywords: Mathematics; Problem-posing; Problem-solving; Attitude; Validity; Reliability; FIT INDEXES; TEACHERS; INSTRUCTION; CHALLENGES; FRACTIONS; SCALE